Favorite children's stories from China (Beijing : Foreign language Press, 1983)
Collects popular Asian folk tales including "How the Cock Got His Red Crown," "The Tower That Reached from Earth to Heaven," and "The Tiger in Court."
Tower that reached from Earth to heaven -- Chinese Cinderella -- Fox turns a somersault -- Tiger in court -- Story of the Fairy boat -- Country of mice -- How the cock got his red crown -- Wishing cup -- Story of the tortoise and the monkey -- Magic pancakes at the Footbridge tavern -- Soo Tan the tiger and the little green frog -- Fox, the hare, and the toad have an argument -- Hungry wolf -- Cricket fight -- Little Hare's clever trick -- King of the mountain -- Jackals and the tiger -- How the deer lost his tail.
Keywords: Islam